ADSORPTION OF ETHYLENE USING COBALT OXIDE-LOADED PILLARED CLAY - Satwikanitya, Pani; Prasetyo, Imam; Fahrurrozi, Moh.; Ariyanto, Teguh (Journal of Engineering and Technological Sciences, 2020)
Clay is an abundant material that is widely used as an adsorbent in pristine or pillared form. Pillared clays feature better properties, e.g. higher specific surface area, thus they can adsorb a higher quantity of adsorbates compared to pristine material. In this work, a preparation of pillared clay using Indonesian natural bentonite and its potential for ethylene removal are presented. The novelty is that a pillaring agent of cobalt (mixed with aluminum) was used, which not only served as a pillar but also as an active metal adsorbent for ethylene. Natural bentonite was pillared using Al (NO3)3.9H2O and Co (NO3)2.6H2O. The resulting material was then calcined at 250 °C. The final material was characterized by N2-sorption analysis, scanning electron microscopy (SEM), and energy dispersive X-ray (EDX) analysis. The cobalt to aluminum ratios used were 1:9, 1:3, 1:1, 1:1/3, and 1:0. From characterization, the Co-Al pillared bentonite featured a specific surface area of up to 114 m2/g (pristine bentonite = 42 m2/g). In the adsorption test, an enhanced ethylene uptake of up to 6 times (at ambient temperature) compared to pristine bentonite was obtained. Thus, the results highlight the potential of cobalt oxide/pillared clay as ethylene scavenger.